Effects of leading-edge defects of the NACA 0015 airfoil on aerodynamic performance with various Reynolds number - Ulfa Hanifah Nurhaliza; James Julian; Fitri Wahyuni; Waridho Iskandar (University of Muhammadiyah Malang, 2023)
This study investigates and identifies the effects produced by defect on an airfoil when compared to a smooth airfoil. The defect used in this research is of the surface concaved defect (SDD) type, with a deep defect characterized by a smooth sunken deformation. The opening size used is t*=12%, and the equivalent depth of the defect is h*=3%. Computational methods are being used in this research to analyzing flow of the fluid through the NACA 0015 airfoil, both in smooth and defective airfoil, with various Reynolds Number which are 1.6×106, 2×106, and 2.5×106. Standard k-epsilon model is being used in this research as turbulence model. For the smooth airfoil, stall conditions occur at an AoA of 11º, while for the defective airfoil, they occur at an AoA of 9^° for each Re variation. The average decrease in the Cl/Cd ratio from smooth airfoil to defective airfoil at each AoA for all Re variations is 33%. There is an increase in pressure on the upperside leading edge of defective airfoil for all Re values. Based on the velocity streamlines, vortices can be found at the defect cavity, and the vortex at the defective airfoil seems larger than the smooth airfoil.